Review of Blockchain Technology on Data Security and Privacy: Recommendations for Advancing Tanzania’s ICT Sector - Kumbo, Lazaro Inon; Mahuwi, Deogratias Tasilo; Hayuma, Bernad Joseph; Nkwera, Victor Simon; Ntyangiri, Christopher Denis; Mushi, Martin Ludovick (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The rapid growth of the ICT sector has led to increased global data exchange and innovation opportunities. The increased use of technology has brought about concerns regarding data security and privacy which triggered a rising interest in blockchain technology as a potential solution to security challenges. This research endeavours to comprehensively examine the influence of blockchain on data security and privacy inside and outside Tanzanian, filling the gap that exists. The blended approach was used to analyse blockchain’s effects while focusing on ethical considerations. The review emphasizes the benefits of blockchain in enhancing data security, trust, and transparency, along with its various applications. The research highlights blockchain technology’s potential to offer robust data protection and improve transparency while identifying the challenges that must be addressed for successful implementation. The study investigates the role of blockchain in securing information systems in global and Tanzanian settings, focusing on sectors such as healthcare, banking, education, and land registration. The study emphasises the significant potential of blockchain technology to impact various industries in Tanzania profoundly. It offers valuable insights for professionals, policymakers, and researchers, highlighting the need to investigate how blockchain can be applied explicitly within different sectors. Additionally, it suggests practical strategies for seamlessly integrating this technology, considering the unique challenges the Tanzanian ICT sector encounters.